“Fiction is the utmost place of the human… it is the place of freedom”: a conversation with Eduardo Moreira and Inês Peixoto (Grupo Galpão) about Moscow (2008) - Mesquita, Cláudia (2024)
Interview with actors Eduardo Moreira and Inês Peixoto, members of Grupo Galpão, about the process of making Moscow (Eduardo Coutinho, 2008), in which Coutinho recorded fragments of the group rehearsing Chekhov's Three Sisters, directed for the stage by Enrique Diaz. They discuss the open-ended nature of the process, Eduardo Coutinho's role in it, the workshops and exercises to develop subtext for the actors, and the inclusion of Chekhov in Galpão's repertoire.